The analysis of junior high school students’ mathematical literacy: Field study in Bandar Lampung - Nurhanurawati, Nurhanurawati; Caswita, Caswita; Bharata, Haninda; Widyastuti, Widyastuti (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Mathematical literacy is a person's ability to formulate, apply and interpret mathematics in various contexts, including the ability to reason systematically and use concepts, procedures, and facts to describe, explain or predict an event. Therefore, mathematical literacy is essential in everyday life. This article analyzed the mathematical literacy of junior high school students in Bandar Lampung. Data were collected by giving mathematical literacy questions to junior high school students. The data were analyzed descriptive–quantitatively. The research population is 14–15 years junior high school students in Bandar Lampung City. The research sample was selected using a stratified sampling technique to get students from several favorable and unfavorable public and private junior high schools. The research instrument was a test on the mathematical literacy of junior high school students. The results showed that junior high school students in Bandar Lampung were generally able to solve mathematical literacy problems whose information was clearly available, solve problems procedurally, and use basic algorithms, formulas, procedures, or conventions involving integers. However, they have yet to solve problems that involve constraints or make assumptions. They have not been able to select and integrate different representations, including symbolic ones, relate them directly to aspects of real–world situations and have not been able to solve problems related to everyday life that they rarely encounter.